The Effect of Giving Probiotics Through Drinking Water To The Weight and Commercial Cuts of The Broiler Carcasses - I. N, Prawira; Suasta, I M.; Astawa, I P. A. (Jurnal Peternakan Tropika, 2019)
This study aims to examine the carcass weights and part of broiler carcasses fed with probiotics through drinking water. Held in a cage owned by Mr. I Made Arcana, located in the village of Candikusuma, Jembrana, for 4 weeks. The study was conducted using a Completely Randomized Design (CRD) consisting of four treatments, namely: P0 (drinking water without the addition of probiotics as a control), P1 (drinking water + probiotics as much as 0.5 ml / 1 liter), and P2 (drinking water + probiotics as much as 1 ml / 1 liter), and P3 (drinking water + probiotics as much as 1.5 ml / 1 liter).  Each treatment consisted of four replications and each replication used 20 DOC CP 707 strains with an average body weight of 49.27 ± 0.90 g. The observed variables were slaughter weight, carcass weight, percentage of carcass, and percentage part of carcass breast, upper thigh, lower thigh, wing, and back. The results showed that the treatment of P1, P2, and P3 could increase slaughter weight, carcass weight and percentage of carcass, statistically significant different (P <0.05). While the breast percentage, upper thigh percentage, lower thigh percentage, back percentage and wing percentage are statistically different insignificant results (P> 0.05). Based on the results of this study it can be concluded that of probiotics (EM-4) at the level of 0.5 - 1.5 ml / 1 liter of drinking water can increase the slaughter weight, carcass weight, and carcass percentage, and no significant effect on part of broiler carcass at 4 weeks.   Keywords : Probiotics, Broiler, Carcasses, Carcasses Percentage.